2002
DOI: 10.1007/s00244-001-0048-8
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Environmental Contaminants in Human Follicular Fluid, Serum, and Seminal Plasma of Couples Undergoing In Vitro Fertilization

Abstract: Environmental chemicals are thought to adversely affect human reproductive function, however there are no studies that have explored the association between failed fertilization and exposure of both partners to environmental contaminants. Therefore, we collected blood and follicular fluid from the female partner and seminal plasma from the male partner of 21 couples attending an in vitro fertilization (IVF) program, in order to determine the extent of the existence of environmental chemicals in these fluids. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
127
4
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(139 citation statements)
references
References 36 publications
6
127
4
2
Order By: Relevance
“…There are several reports regarding the presence of some POPs, such as dioxins, dibenzofurans, and the dioxin-like PCBs, organochlorinated pesticides, in semen or seminal plasma (Kumar et al, 2000;Pant et al, 2007;Schecter et al, 1996;Younglai et al, 2002). In the present study, we found for the first time the presence of PBDEs in human semen and demonstrated that PBDEs could enter human semen like other POPs.…”
Section: Pbde Concentration In Human Semen Compared With In Human Bloodsupporting
confidence: 67%
“…There are several reports regarding the presence of some POPs, such as dioxins, dibenzofurans, and the dioxin-like PCBs, organochlorinated pesticides, in semen or seminal plasma (Kumar et al, 2000;Pant et al, 2007;Schecter et al, 1996;Younglai et al, 2002). In the present study, we found for the first time the presence of PBDEs in human semen and demonstrated that PBDEs could enter human semen like other POPs.…”
Section: Pbde Concentration In Human Semen Compared With In Human Bloodsupporting
confidence: 67%
“…A prior investigation of 619 Saudi Arabian IVF patients reported a positive yet nonsignificant association between FF Pb and oocyte fertilization (OR0 1.45, 95%CI 0.69-3.02), with a 'borderline-significant' positive association for FF Cd (OR01.87, 95%CI 0.91-3.82) in the same logistic regression model including 19 covariates [7]. An earlier, and smaller study reported significantly higher FF Cd concentrations for three Canadian IVF patients who achieved pregnancy, compared to three IVF patients with no fertilized oocytes [15]. Our FF Cd results are consistent with prior publications reporting a positive association with fertilization, yet our FF Pb results are inconsistent with the single prior study reporting an association.…”
Section: Associations Between Metals and Oocyte Fertilizationmentioning
confidence: 99%
“…However, the aforementioned Saudi Arabian IVF study reports an inverse association between blood Cd and the number of 'poor embryos' (r0−0.09, P00.04), yet no association was found for FF Hg, Cd or Pb [7]. In addition, the earlier Canadian IVF study reported no association between measured FF Cd and embryo quality [15]. Embryotoxic effects have been reported following embryo treatment in vitro with low levels of Cd and Pb in the experimental literature [44,45].…”
Section: Associations Between Metals and Embryo Qualitymentioning
confidence: 99%
See 2 more Smart Citations